Dimensi Spiritual Bulan Haram dalam Al-Qur’an: Analisis Tafsir Q.S. At-Taubah: 36 dan Momentum Muharram 1448 H: The Spiritual Dimension of the Sacred Months in the Qur'an: An Exegetical Analysis of Surah At-Tawbah (9:36) in the Momentum of Muharram 1448 H - Teuku Muhammad Fauzan Robbani (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2026)
This study aims to deeply analyze the spiritual dimension of the sacred months based on the tafsir of surah At-Taubah verse 36, particularly on the momentum of welcoming the Muharram 1448 H New Year. The research method used is descriptive qualitative with a literature study (library research) approach, based on the Tafsir Maudhui (thematic) analysis method to synthesize data comprehensively. The results of this study show that the prohibition of wronging oneself (do not wrong yourselves) in the sacred months indicates the importance of self-control from negative behaviors, maintaining mental health against social anxiety or insecurity, and avoiding an excessively consumptive lifestyle. This spiritual dimension can be actualized through the application of the concept of taqwa, a simple lifestyle (frugal living), and prioritizing spiritual wealth (inner wealth) over material goods. The momentum of Muharram 1448 H should serve as a means of collective self-reflection and strengthening da'wah values in Indonesia to cultivate true piety. This research contributes theoretically to the Qur'anic studies treasury by offering practical and spiritual solutions that are highly relevant to address the socio-psychological challenges of modern society.